2014
DOI: 10.3126/on.v11i2.9646
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Growth and Production of Nile Tilapia (Oreochromis niloticus) Fingerlings Relative to Phytoplankton and Periphyton Biomass

Abstract: The growth, production and survival of Nile tilapia Oreochromis niloticus, with an average individual weight of 0.2 g were used to determine the density-dependent growth and production relative to phytoplankton and periphyton biomass in periphyton-based aquaculture. The trial was conducted in 10 m 2 concrete tanks for a 56 day period. A 10 cm layer of soil was placed at the bottom of each tank. To act as substrates for periphyton, bamboo poles with an approximate submerged surface area of 50% to that of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Many fish in nature as well as in culture relies on periphyton for its food. Indian major carp (Wahab et al, 1999;Ramesh et al, 1999;Rai et al, 2010), tilapia (Hem and Avit, 1994;Shrestha and Knud-Hansen, 1994;Milstein et al, 2009: Jiwyam, 2013, common carp (Rai and Yi, 2012) as well prawn (Udin et al, 2007) prefer periphyton as natural food. Previous study on periphyton based carp polyculture in Nepal showed a promising result with an increase of 24% in fish yield (Jha et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many fish in nature as well as in culture relies on periphyton for its food. Indian major carp (Wahab et al, 1999;Ramesh et al, 1999;Rai et al, 2010), tilapia (Hem and Avit, 1994;Shrestha and Knud-Hansen, 1994;Milstein et al, 2009: Jiwyam, 2013, common carp (Rai and Yi, 2012) as well prawn (Udin et al, 2007) prefer periphyton as natural food. Previous study on periphyton based carp polyculture in Nepal showed a promising result with an increase of 24% in fish yield (Jha et al, 2018).…”
Section: Introductionmentioning
confidence: 99%